Challenges and Prospects of National Security, Legitimacy, and Democratic Sustenance in Nigeria's Fourth Republic - Abdullahi Abiodun Oyekanmi; Mushrafa Olapeju Rosenje (Journal of Government and Political Issues, 2022)
This study investigates the challenges of national security, legitimacy, and democratic sustenance in Nigeria's Fourth Republic, which are critical aspects of governance that affect the stability of democratic countries. Utilizing a desk research method, the paper gathers and contently analyzes secondary materials, including academic journals, case reports, published textbooks, and online sources, employing the failed states theory as the explanatory framework. The research identifies key challenges affecting Nigeria's democratic sustainability, such as inherited colonial security orientation, Boko Haram insurgency, herdsmen clashes, banditry, ethnicity, separatist agitations, underdevelopment, and electoral malpractices. Based on these findings, the paper recommends a comprehensive review of the national security apparatus, emphasizing people's welfare through good governance, public enlightenment on the values of democracy, and the importance of supporting and protecting democratic institutions. This study contributes to understanding the complex interplay between national security, legitimacy, and democratic sustenance in the context of Nigeria and offers potential solutions for addressing these challenges.